Trends in Cosmetics: Product Packaging at the Point of Sale - Belén Borja Guerrero; Aránzazu López Pecharromán; Rosario C. Sánchez León (Cosmetics, 2022)
Recently, there has been a proliferation of establishments where cosmetics products are packaged at the purchaser’s request, promoting the circular economy with the aim of reusing, recycling and reducing packaging. At the Spanish Agency of Medicines and Medical Devices (AEMPS, for its Spanish acronym), we asked ourselves whether this was a legal and safe practice. In order to verify this, a bibliographic analysis of the applicable legislation and regulations was carried out, and the conclusion reached was that it is legal practice, but a series of guidelines are necessary for it to be carried out with guarantees. Consequently, an instruction was developed which provides recommendations to ensure that the packaging of cosmetic products at the point of sale is carried out under optimum conditions. This instruction is aimed at both responsible persons and the personnel who carry out product packaging at the point of sale.